218k views
4 votes
Sail with the equation by completing the square x^2+8x=-3

User Kaiyuan Xu
by
5.0k points

1 Answer

4 votes

Answer:

The solutions are
x=-4(+/-)√(13)

Explanation:

we have


x^(2) +8x=-3

Complete the square. Remember to balance the equation by adding the same constants to each side


x^(2) +8x+16=-3+16


x^(2) +8x+16=13

Rewrite as perfect squares


(x+4)^(2)=13

square root both sides


x+4=(+/-)√(13)


x=-4(+/-)√(13)

User Akhil Soman
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.